Analisis Penerimaan Layanan Insurtech Shopee sebagai Aplikasi Mobile Marketplace Berdasarkan Model TAM - Ida Lestari; Riyo Riyadi; Indah Permatasari; Kadori Haidar (Program Studi Teknik Informatika Universitas Pamulang, 2025)
Students of Economics Education at Mulawarman University are part of Generation Z, and they benefit from insurtech innovations like Shopee's product damage protection. Despite the service's usefulness and ease of use, its intention to be reused is low. Perceived utility and perceived ease of use, as measured by use attitude, impact behavioral intention to use, according to the Technology Acceptance Model (TAM). A total of 104 pupils who have made use of Shopee's insurtech services are a part of this quantitative study's route analysis. Information was gathered by means of surveys and analyzed with the help of STATA version 13. The findings show that behavioral intention to use is somewhat affected by perceived ease of use and using attitude, but not by perceived usefulness. Furthermore, among Economics Education students at Mulawarman University, use attitude is indirectly affected by behavioral intention to use via perceived utility and perceived ease of use of Shopee's insurtech services, and vice versa. Management Information Systems (MIS) play an important element in understanding how people embrace digital financial services powered by technology, especially insurtech markets, and what this means for creating user-adaptive systems of information.